Gaya Komunikasi Calon Kepala Daerah Menjelang Pilkada Pada Media Sosial Instagram - Renata Anisa (Sosioglobal, 2018)
The election of head of region in Indonesia will be held in June 2018, the candidates compete to get public attention and sympathy with communication through social media. On social media, the candidates can informs the vision, mission, programs, accommodate the public aspirations, and communicate directly to the public with style of communication of each candidates.This research aims to find how communication style used by the candidate ahead of the elections on instagram. This research uses ethnographic virtual method by analyzing communication style that used a candidate's  in communicating with netizen. This research uses observation and participation in the study of literature in the process of data collection.The results showed that communication style used by the candidate Ridwan Kamil on social media instagram ia a two way communication style (The Equalitarian Style). It can be seen from the communication and the delivery of messages that are two-way. Communication conducted informal and open, where the netizen can access the candidate account and expressed their opinion, criticism, ideas, and support directly. The candidate using social media to communicate with public directly, describe their programs, information visits to regions, election debate agenda information, and other activities. On any information uploaded by RK account is able to acquire as many as a hundred netizen comments up to four thousand both positive and negative.